MATHEMATICS
MIDDLE SCHOOL

Answer: Easy. Follow my steps:

Combine Like terms

Then, add-2 to both sides.

Then divide.

Answer: x=0

Combine Like terms

Then, add-2 to both sides.

Then divide.

Answer: x=0

Answer: 1x+2y+2=1x+2y+2

And your answers is all real numbers

And your answers is all real numbers

MIDDLE SCHOOL

The rational roots of a polynomial function f(x) can be written in the form p/q, where p is a factor of the leading coefficient of the polynomial and q is a factor of the constant term. A true

B false

Answer: A

Step-by-step explanation:

HIGH SCHOOL

A stick is broken into two pieces, at a uniformly random break point. Find the CDF and average of the length of the longer piece.

Answer:

P(L ≤ l) =P (1-l ≤ U ≤ l)= l- ( 1 - l ) = 2 l - 1

Step-by-step explanation:

let assume that stick has length 1.Random variable L that make length of a longer piece and random variable U that mark point .See that L < l means that

U≤ l and 1-U ≤l

P(L ≤ l) =P (1-l ≤ U ≤ l)= l- ( 1 - l ) = 2 l - 1

this means 1-l≤U≤l

so we have

if we have L [1/2,1]

then apply the formula we have E(L)=3/4

MIDDLE SCHOOL

What are the zeros of f(x) = (x − 7)(x − 3)(x − 2)? Question 3 options: 7, −3, 2 7, −3, �2 7, 3, 2 7, 3, −2

Answer:

7, 3, and 2

Step-by-step explanation:

to get zeros, you need to multioly multiply something by 0. That means that one of the 3 parts has to be 0. Either x-7 = 0 or x-3 or x-2. set each equal to 0 and solve to get x = something. those answers are zeros and are 7, 3, and 2

Answer:

C

Step-by-step explanation:

7,3, and 2

HIGH SCHOOL

What is the solution set of (x - 2)(x - 3) = 2?

a. {1, 4}

b. {2, 3}

c. {4, 5}

Step One

Remove the brackets. Use Foil

F: x^2

O: -3x

I: -2x

L:(-2)(-3) = 6

What you have now is

x^2 - 3x - 2x + 6 = 2

Step Two

Combine like terms.

x^2 - 5x + 6 = 2

Step Three

Subtract 2 from both sides.

x^2 - 5x + 6 - 2 = 0

x^2 - 5x + 4 = 0

Step 4

Factor

(x - 4)(x - 1) = 0

Step 5

Find the zeros.

x - 4 = 0

x = 4

x -1 = 0

x = 1

Solution Set

(1,4)

Remove the brackets. Use Foil

F: x^2

O: -3x

I: -2x

L:(-2)(-3) = 6

What you have now is

x^2 - 3x - 2x + 6 = 2

Step Two

Combine like terms.

x^2 - 5x + 6 = 2

Step Three

Subtract 2 from both sides.

x^2 - 5x + 6 - 2 = 0

x^2 - 5x + 4 = 0

Step 4

Factor

(x - 4)(x - 1) = 0

Step 5

Find the zeros.

x - 4 = 0

x = 4

x -1 = 0

x = 1

Solution Set

(1,4)